The bankruptcy of the foreign investor in the GCC system under the Model Law on Cross-Border Insolvency - Hadi, Zubaida Abdel (Journal of Economic, Administrative and Legal Sciences, 2018)
The bankruptcy has a vital role in supporting the commercial liability, because it forms guarantee to fulfilment the debtor to his loans on time of dues by crushing him and preventing him to damage creditors, so this study aimed to recognize the law applied on the rule by bankruptcy of the foreign investors in the systems of the Gulf Cooperation Council (GCC), in frame of the regional agreements and the model law for insolvency across the borders, the study is interested with the systems of the Gulf Cooperation Council (GCC) because they adopt recently in its internal commercial systems, the policies of the economy opening and seeking to motivation and attraction the foreign investments with joining the international commercial agreements. The study used the analytical descriptive approach by following and analysing the systems of insolvency in these countries with a try to consideration them, the results of the study referred to adoption the systems of the gulf cooperation council to the private agreement for implementation the rule of insolvency in any country from its countries with regard to its citizens only with exclusion the other foreigners. With the possibility to issue rule of announcement insolvency of the foreigners the non-citizens of the Gulf Cooperation Council (GCC), despite the existence of monies of the debtor in other foreign country, but the rule collides with the none of its implementation in the foreign country, and there are some of the submitted recommendations and the important ones as follows: The necessity to remove all the lawful and action obstacles that prevent the accreditation of the model law of uniserial related with insolvency across the borders in Gulf Cooperation Council (GCC).